2021
DOI: 10.1101/2021.06.21.449213
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diversity and evolution of pigment types and the phycobilisome rod gene region of marine Synechococcus cyanobacteria

Abstract: Synechococcus picocyanobacteria are ubiquitous and abundant photosynthetic organisms in the marine environment and contribute for an estimated 16% of the ocean net primary productivity. Their light-harvesting complexes, called phycobilisomes (PBS), are composed of a conserved allophycocyanin core from which radiates six to eight rods with variable phycobiliprotein and chromophore content. This variability allows Synechococcus to optimally exploit the wide variety of spectral niches existing in marine ecosystem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 96 publications
(189 reference statements)
0
2
0
Order By: Relevance
“…Phylogeny of PBS rods gene region showed that different clades that possessed one same PT could not be distinguished well in previous studies (Xia et al, 2017b(Xia et al, , 2018Grébert et al, 2018). However, Grébert et al (2021a) indicated that, for a given PT, the tree topology of mpeBA phylogeny actually resembled the topology based on the core gene petB although some exceptions existed due to inter-clade lateral gene transfers, suggesting the divergence of PBS rods gene region between different clades possessing the same PT. In this study, the niche partitioning of various ESTUs was possibly resulted from potential divergence between different phylogenetic clades that possessed the same PT but occupied different habitats.…”
Section: Niche Partition and Divergence Of Pigment Typesmentioning
confidence: 71%
See 1 more Smart Citation
“…Phylogeny of PBS rods gene region showed that different clades that possessed one same PT could not be distinguished well in previous studies (Xia et al, 2017b(Xia et al, , 2018Grébert et al, 2018). However, Grébert et al (2021a) indicated that, for a given PT, the tree topology of mpeBA phylogeny actually resembled the topology based on the core gene petB although some exceptions existed due to inter-clade lateral gene transfers, suggesting the divergence of PBS rods gene region between different clades possessing the same PT. In this study, the niche partitioning of various ESTUs was possibly resulted from potential divergence between different phylogenetic clades that possessed the same PT but occupied different habitats.…”
Section: Niche Partition and Divergence Of Pigment Typesmentioning
confidence: 71%
“…The phylogenetic divergence of ESTUs within one PT was most likely due to the niche partitioning of various clades possessing the given PT. It was estimated that the divergence of PBS resulted from lateral gene transfer events, whereas PBS rods gene region apparently possessed an evolution history different from that of the core genome (Six et al, 2007;Grébert et al, 2021a). Phylogeny of PBS rods gene region showed that different clades that possessed one same PT could not be distinguished well in previous studies (Xia et al, 2017b(Xia et al, , 2018Grébert et al, 2018).…”
Section: Niche Partition and Divergence Of Pigment Typesmentioning
confidence: 93%
“…In this context, Synechococcus cells capable of CA4, i.e., to match their Exc 495:545 ratio to the ambient light color in order to optimize photon collection, expectedly colonize both blue and green niches, where they can constitute a large part of the whole Synechococcus population, especially at high latitude (Xia et al, 2017; , 2018). The of two genetically distinct types of chromatic acclimaters colonizing different habitats in the field (Humily et al, 2013;Grébert et al, 2018Grébert et al, , 2021Grébert et al, , 2022 however made us wonder whether they displayed phenotypic differences that may partly explain their different spatial distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly in this context, the WH8109 strain that was reported to display this fixed phenotype in Humily et al (2013) was found to have recovered its CA4 ability in a more recent study (Lovindeer et al, 2021). The wider phenotypic variability observed in PT 3dA representatives might be attributed to the erratic genomic localization of the CA4-A island, which can be found virtually anywhere in the genome of PT 3dA strains, including the 5′-end of the PBS region, while the CA4-B island is systematically located in the middle of the PBS rod region in PT 3dB cells (Humily et al, 2013;Grébert et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation